Low-humidity cured dealcoholized silicone sealant and preparation method thereof
By adopting specific crosslinking agent and coupling agent processes in dealcohol type silicone sealant, the concentration of functional groups and hydrolysis reaction efficiency are improved, and the problems of slow curing and low bonding strength in low temperature and low humidity environments in winter are solved. , faster curing and higher bonding strength, and improved construction efficiency.
Patent Information
- Application Number
- CN202411739317.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The existing dealcoholized silicone sealant has problems such as slow deep curing, long debonding time and low initial bonding strength in low temperature and low humidity environments in winter, which affects construction efficiency.
Using specific crosslinking agents and coupling agent processes, crosslinking agents and coupling agents are selected to combine reflux activation, and a specific proportion of high-active coupling agents can increase the concentration of functional groups and promote the hydrolysis reaction to consume less water. In turn, the coupling bonding speed and initial bonding strength are improved.
It significantly improves the cross-linking curing speed and initial bonding speed in low-humidity environments, improves the initial bonding strength, shortens the maintenance time, and improves construction efficiency.
Smart Images

Figure CN119432313A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of silicone sealants, and in particular relates to a low-humidity curing dealcoholization type silicone sealant and a preparation method thereof. Background Art
[0002] Condensation type one-component room temperature vulcanized (RTV-1) silicone sealant is a paste made of terminal hydroxyl polydimethylsiloxane as the base polymer, supplemented with fillers, plasticizers, crosslinking agents, coupling agents, catalysts, etc., mixed in a moisture-proof container. It solidifies into an elastomeric silicone rubber by reacting with water in the air at room temperature. Silicone sealant has the advantages of high and low temperature resistance, weather aging resistance, electrical insulation, non-toxicity and physiological inertness, while dealcoholized silicone sealant has the characteristics of no irritating odor and no corrosion to the substrate, and is widely used in construction, home decoration, electronic appliances and other industries.
[0003] For example, a Chinese patent document with publication number CN117447506A discloses a modifier, modified nano calcium carbonate, dealcoholized silicone sealant and a preparation method thereof. The modifier is obtained by reacting tris[3-(trimethoxysilyl)propyl]isocyanurate with hydroxymethyldiphenylsilane. The modified nano calcium carbonate is obtained by reacting the modifier with nano calcium carbonate. The filler in the one-component dealcoholized silicone sealant is the modified nano calcium carbonate. The invention prepares a modifier by heating and stirring tris[3-(trimethoxysilyl)propyl]isocyanurate and hydroxymethyldiphenylsilane, and uses the modifier to perform surface treatment and modification on nano calcium carbonate, and then uses the modified nano calcium carbonate in the one-component dealcoholized silicone sealant, which can effectively reduce the adhesion between the colloids, so that the anti-drawing performance of the silicone sealant is significantly improved.
[0004] The curing of condensation-type one-component silicone sealant needs to absorb moisture from the air and gradually cure from the outside to the inside. Existing dealcohol-type silicone sealants generally have shortcomings such as slow deep curing, long detackification time, and low initial bonding strength. These shortcomings are particularly evident in the low temperature and low humidity environment in winter, which greatly affects the construction efficiency.
[0005] Therefore, to address this problem, it is necessary to develop a dealcoholized silicone sealant with good hygroscopicity, high water vapor permeability during the curing process, short detackification time, fast deep curing, fast initial bonding speed and high strength. Summary of the invention
[0006] The technical problem solved by the present invention is to provide a low-humidity curing dealcoholized silicone sealant and a preparation method thereof, aiming to solve the common problems of existing dealcoholized silicone sealants, such as slow deep curing, long detackification time, low initial bonding strength, etc.
[0007] In order to solve the above problems, the first aspect of the present invention provides a low-moisture curing dealcoholization type silicone sealant, comprising the following components in parts by mass:
[0008] 100 parts of α,ω-dihydroxy polydimethylsiloxane, 70-140 parts of nano calcium carbonate, 3-10 parts of dimethyl silicone oil, 1-4 parts of modified silicone oil, 3-10 parts of composite cross-linking agent, 0.5-2 parts of coupling agent A, 0.5-1.5 parts of coupling agent B, 2-6 parts of titanate catalyst;
[0009] Wherein, the coupling agent A is one or a mixture of γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane, γ-aminopropyltrimethoxysilane, and γ-aminopropylmethyldiethoxysilane;
[0010] The coupling agent B is one or a mixture of epoxy silane oligomer and amino silane oligomer, and the structure of the coupling agent B is shown in the following formulas Ⅰ, Ⅱ, and Ⅲ, wherein n=0-4 in formula Ⅰ; n=0-4 in formula Ⅱ; and n=4-6 in formula Ⅲ;
[0011]
[0012] The mass ratio of the coupling agent A to the coupling agent B is 0.9-1.3:1.
[0013] Preferably, the composition comprises the following components in parts by mass: 100 parts of α,ω-dihydroxypolydimethylsiloxane, 120-140 parts of nano calcium carbonate, 4-6 parts of dimethyl silicone oil, 1-2 parts of modified silicone oil, 5-7 parts of composite cross-linking agent, 0.8-1.5 parts of coupling agent A, 0.8-1.2 parts of coupling agent B, and 3-5 parts of titanate catalyst.
[0014] Preferably, the following components are included in parts by mass: 100 parts of α, ω-dihydroxypolydimethylsiloxane, 120 parts of nano calcium carbonate, 5 parts of dimethyl silicone oil, 2 parts of modified silicone oil, 6 parts of composite crosslinking agent, 0.8 parts of coupling agent A, 1.2 parts of coupling agent B, and 4 parts of titanate catalyst.
[0015] Preferably, the structure of the modified silicone oil is as shown in Formula IV:
[0016]
[0017] Preferably, the mass ratio of the dimethyl silicone oil to the modified silicone oil is 2.5-4:1.
[0018] Preferably, the viscosity of the α,ω-dihydroxypolydimethylsiloxane is 20000-80000 mPa·s; and the particle size of the nano-calcium carbonate is 50-200 nm.
[0019] Preferably, the viscosity of the dimethyl silicone oil is 300-500 mPa·s; the modified silicone oil is polyethylene glycol-modified hydroxy silicone oil, and the viscosity is 300-800 mPa·s.
[0020] Preferably, the titanate catalyst is one or a mixture of diisopropoxybis(ethoxyacetoacetyl)titanium, di-n-butoxybis(ethoxyacetoacetyl)titanium and tetraisopropyl titanate; the crosslinking agent is at least two of ethyl orthosilicate, propyl orthosilicate, polyethyl silicate, methyltrimethoxysilane, methyltriethoxysilane and polymethyltriethoxysilane oligomers.
[0021] The second aspect of the present invention provides a method for preparing the low-humidity curing dealcoholization type silicone sealant as described above, comprising the following steps:
[0022] S1: mixing α,ω-dihydroxy polydimethylsiloxane, dimethyl silicone oil and nano calcium carbonate to obtain a base material;
[0023] S2: mixing the composite cross-linking agent and the coupling agent A to obtain a mixed treated product;
[0024] S3: mixing the base material, modified silicone oil, the mixed treated product, coupling agent B, and titanate catalyst to obtain a low-humidity curing dealcoholization type silicone sealant.
[0025] Preferably, step S1 specifically comprises the following steps: adding the α,ω-dihydroxy polydimethylsiloxane, the dimethyl silicone oil and the nano calcium carbonate into a kneader at a temperature of 100°C to 150°C and a vacuum degree of -0.09 to -0.1 MPa, dehydrating and blending for 2 to 3 hours to obtain a base material, and cooling for standby use;
[0026] Step S2 specifically includes the following steps: stirring and refluxing the composite cross-linking agent and the coupling agent A at 100° C. to 120° C. for 12 to 48 hours, and then cooling to 30° C. to 40° C. to obtain a mixed treated product;
[0027] Step S3 specifically includes the following steps: at 10 to 30° C., adding the above-mentioned base material, the modified silicone oil, the mixed treated product, the coupling agent B, and the titanate catalyst into a planetary machine and stirring, stirring for 1 to 3 hours at a temperature of 30° C. to 50° C. and a vacuum degree of -0.09 to -0.1 MPa to obtain the low-humidity curing dealcoholization type silicone sealant.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The low-humidity curing dealcoholized silicone sealant of the present invention adopts a specific cross-linking agent and coupling agent process, selects a cross-linking agent and a coupling agent for compounding and reflow activation, and is equipped with a specific proportion of a high-activity coupling agent. It has a high functional group concentration, a low water consumption and a fast hydrolysis reaction, can significantly improve the coupling bonding speed, and has a high initial bonding strength. In low-humidity winter construction, it can greatly shorten the maintenance time and improve the construction efficiency.
[0030] The low-humidity curing dealcoholization type silicone sealant of the present invention is a hygroscopic silicone sealant. After being exposed to the air, it can quickly absorb the water vapor required for the hydrolysis reaction of the cross-linking agent and the coupling agent, promote cross-linking curing and coupling bonding, meet the requirements of winter construction, and improve the efficiency of winter construction. DETAILED DESCRIPTION
[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] A first aspect of an embodiment of the present invention provides a low-moisture curing dealcoholization type silicone sealant, comprising the following components in parts by weight:
[0033] 100 parts of α,ω-dihydroxy polydimethylsiloxane, 70-140 parts of nano calcium carbonate, 3-10 parts of dimethyl silicone oil, 1-4 parts of modified silicone oil, 3-10 parts of composite cross-linking agent, 0.5-2 parts of coupling agent A, 0.5-1.5 parts of coupling agent B, 2-6 parts of titanate catalyst;
[0034] Wherein, the coupling agent A is one or a mixture of γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane, γ-aminopropyltrimethoxysilane, and γ-aminopropylmethyldiethoxysilane;
[0035] The coupling agent B is one or a mixture of epoxy silane oligomer and amino silane oligomer, and the structure of the coupling agent B is shown in the following formulas Ⅰ, Ⅱ, and Ⅲ, wherein n=0-4 in formula Ⅰ; n=0-4 in formula Ⅱ; and n=4-6 in formula Ⅲ;
[0036]
[0037] The mass ratio of the coupling agent A to the coupling agent B is 0.9-1.3:1.
[0038] The low-humidity curing dealcoholized silicone sealant of the embodiment of the present invention is a hygroscopic silicone sealant, and the polyethylene glycol-modified hydroxy silicone oil (structure as Formula IV) is evenly dispersed in the system, and its polyether segment has good hydrophilicity and hygroscopicity. When the silicone sealant is exposed to the air, it can quickly absorb the water vapor required for the hydrolysis reaction of the crosslinking agent and the coupling agent, promote crosslinking curing and coupling bonding, meet the requirements of winter construction, and improve winter construction efficiency.
[0039] The low-humidity curing dealcoholization type silicone sealant of the embodiment of the present invention adopts a silane coupling agent and a specific high-activity coupling agent compound, and adopts a specific cross-linking agent compound, and has a high functional group concentration, a low water consumption in the hydrolysis reaction, and a fast process. Using a silane monomer coupling agent with a high functional group concentration, its hydrolysis coupling process consumes a lot of water and the process is slow, the initial adhesion is poor, and the initial bonding strength decreases. The present invention adopts a hygroscopic modified silicone oil and a cross-linking agent coupling agent system of a specific process, and the resulting dealcoholization type silicone sealant has a faster cross-linking curing speed, a faster initial bonding speed, and a higher initial bonding strength in a low-humidity environment, and can significantly improve the coupling bonding speed, and the initial bonding strength is high. In low-humidity winter construction, the maintenance time can be greatly shortened and the construction efficiency can be improved.
[0040] In some embodiments, the following components are included in parts by mass: 100 parts of α, ω-dihydroxypolydimethylsiloxane, 120-140 parts of nano calcium carbonate, 4-6 parts of dimethyl silicone oil, 1-2 parts of modified silicone oil, 5-7 parts of composite cross-linking agent, 0.8-1.5 parts of coupling agent A, 0.8-1.2 parts of coupling agent B, and 3-5 parts of titanate catalyst.
[0041] In some embodiments, the following components are included in parts by mass: 100 parts of α, ω-dihydroxypolydimethylsiloxane, 120 parts of nano calcium carbonate, 5 parts of dimethyl silicone oil, 2 parts of modified silicone oil, 6 parts of composite cross-linking agent, 0.8 parts of coupling agent A, 1.2 parts of coupling agent B, and 4 parts of titanate catalyst.
[0042] In some embodiments, the structure of the modified silicone oil is as shown in Formula IV:
[0043]
[0044] In some embodiments, the mass ratio of the dimethyl silicone oil to the modified silicone oil is 2.5 to 4:1.
[0045] In some embodiments, the viscosity of the α,ω-dihydroxypolydimethylsiloxane is 20,000 to 80,000 mPa·s; and the particle size of the nano-calcium carbonate is 50 to 200 nm.
[0046] In some embodiments, the viscosity of the dimethyl silicone oil is 300 to 500 mPa·s; the modified silicone oil is polyethylene glycol-modified hydroxy silicone oil, and the viscosity is 300 to 800 mPa·s.
[0047] In some embodiments, the titanate catalyst is a mixture of one or more of diisopropoxybis(ethoxyacetoacetyl)titanium, di-n-butoxybis(ethoxyacetoacetyl)titanium and tetraisopropyl titanate; the crosslinking agent is at least two of tetraethyl orthosilicate, propyl orthosilicate, polyethyl silicate, methyltrimethoxysilane, methyltriethoxysilane, and polymethyltriethoxysilane oligomers.
[0048] A second aspect of an embodiment of the present invention provides a method for preparing the low-humidity curing dealcoholization type silicone sealant as described above, comprising the following steps:
[0049] S1: mixing α,ω-dihydroxy polydimethylsiloxane, dimethyl silicone oil and nano calcium carbonate to obtain a base material;
[0050] S2: mixing the composite cross-linking agent and the coupling agent A to obtain a mixed treated product;
[0051] S3: mixing the base material, modified silicone oil, the mixed treated product, coupling agent B, and titanate catalyst to obtain a low-humidity curing dealcoholization type silicone sealant.
[0052] In some embodiments, step S1 specifically includes the following steps: adding the α,ω-dihydroxy polydimethylsiloxane, the dimethyl silicone oil, and the nano calcium carbonate into a kneader at a temperature of 100° C. to 150° C. and a vacuum degree of -0.09 to -0.1 MPa, dehydrating and blending for 2 to 3 hours to obtain a base material, and cooling for standby use;
[0053] Step S2 specifically includes the following steps: stirring and refluxing the composite cross-linking agent and the coupling agent A at 100° C. to 120° C. for 12 to 48 hours, and then cooling to 30° C. to 40° C. to obtain a mixed treated product;
[0054] Step S3 specifically includes the following steps: at 10 to 30° C., adding the above-mentioned base material, the modified silicone oil, the mixed treated product, the coupling agent B, and the titanate catalyst into a planetary machine and stirring, stirring for 1 to 3 hours at a temperature of 30° C. to 50° C. and a vacuum degree of -0.09 to -0.1 MPa to obtain the low-humidity curing dealcoholization type silicone sealant.
[0055] The low-humidity curing dealcoholized silicone sealant of the embodiment of the present invention adopts a specific cross-linking agent and coupling agent process, selects a cross-linking agent and a coupling agent for compound reflow activation, and is equipped with a specific proportion of a high-activity coupling agent. It has a high functional group concentration, a low water consumption and a fast hydrolysis reaction, can significantly improve the coupling bonding speed, and has a high initial bonding strength. In low-humidity winter construction, it can greatly shorten the maintenance time and improve construction efficiency.
[0056] The α,ω-dihydroxypolydimethylsiloxane used in the following embodiments and comparative examples was purchased from China National Bluestar (Group) Co., Ltd., model 107 glue; modified silicone oil was purchased from Anhui Mingyi Silicon Co., Ltd., model MY 1291; γ-glycidyloxypropyltrimethoxysilane was purchased from Hubei Jianghan New Materials Co., Ltd., model JH-O187; epoxy silane oligomer was purchased from Hubei Jianghan New Materials Co., Ltd., model JH-OP17; aminosilane oligomer was purchased from Hubei Jianghan New Materials Co., Ltd., model JH-AP1234.
[0057] Example 1
[0058] The preparation method of the low-humidity curing dealcoholized silicone sealant of this embodiment comprises the following steps:
[0059] S1: 100 parts of α,ω-dihydroxy polydimethylsiloxane with a viscosity of 50000 mPa·s, 5 parts of dimethyl silicone oil with a viscosity of 300 mPa·s, and 120 parts of 100 nanometer activated calcium carbonate were added to a planetary machine, mixed for 2 hours at 120°C and vacuum -0.095 MPa, and then cooled to 30°C to obtain a base material;
[0060] S2: 3 parts of methyltrimethoxysilane, 3 parts of polymethyltriethoxysilane, and 1 part of γ-glycidyloxypropyltrimethoxysilane were stirred and refluxed at 120° C. for 48 hours, and then cooled to 30° C. in a sealed container to obtain a mixed treated product;
[0061] S3: Add the above base material, 2 parts of modified silicone oil with a viscosity of 500mPa·s (structure as Formula IV), the mixed treated product, 1 part of hydroxy-terminated hexapolyaminoethyliminopropylmethoxysilane (structure as Formula III), and 4 parts of diisopropoxybis(ethoxyacetoacetyl)titanium into a planetary mixer, and stir for 1 hour at 40°C and vacuum -0.09MPa to obtain a dealcoholized silicone sealant.
[0062] Example 2
[0063] The preparation method of the low-humidity curing dealcoholized silicone sealant of this embodiment comprises the following steps:
[0064] S1: 100 parts of α,ω-dihydroxy polydimethylsiloxane with a viscosity of 80000 mPa·s, 6 parts of dimethyl silicone oil with a viscosity of 300 mPa·s, and 90 parts of 100 nanometer activated calcium carbonate were added to a planetary machine, mixed for 2 hours at 120°C and vacuum -0.095 MPa, and then cooled to 30°C to obtain a base material;
[0065] S2: 3 parts of methyltriethoxysilane, 2 parts of propyl orthosilicate, and 1.5 parts of γ-glycidyloxypropyltrimethoxysilane were stirred and refluxed at 120° C. for 48 hours, and then cooled to 30° C. in a sealed container to obtain a mixed treated product;
[0066] S3: Add the above base material, 1.5 parts of modified silicone oil with a viscosity of 500mPa·s (structure as shown in Formula IV), the mixed treated material, 1.2 parts of hydroxy-terminated hexapolyaminoethyliminopropylmethoxysilane (structure as shown in Formula III), and 3 parts of diisopropoxybis(ethoxyacetoacetyl)titanium into a planetary machine, and stir at 40°C and vacuum -0.09MPa for 1h to obtain a dealcoholized silicone sealant.
[0067] Example 3
[0068] The preparation method of the low-humidity curing dealcoholized silicone sealant of this embodiment comprises the following steps:
[0069] S1: 100 parts of α,ω-dihydroxy polydimethylsiloxane with a viscosity of 20000 mPa·s, 4 parts of dimethyl silicone oil with a viscosity of 300 mPa·s, and 140 parts of 100 nanometer activated calcium carbonate were added into a planetary machine, mixed for 2 hours at 120°C and vacuum -0.095 MPa, and then cooled to 30°C to obtain a base material;
[0070] S2: 4 parts of polymethyltriethoxysilane, 3 parts of propyl orthosilicate, and 1 part of γ-aminopropyltrimethoxysilane were stirred and refluxed at 120° C. for 48 hours, and then cooled to 30° C. in a sealed container to obtain a mixed treated product;
[0071] S3: Add the above base material, 1 part of modified silicone oil with a viscosity of 500mPa·s (structure as shown in Formula IV), the mixed treated material, 0.8 parts of hexapolyglycidyloxypropylmethoxysilane (structure as shown in Formula I), and 5 parts of diisopropoxybis(ethoxyacetoacetyl)titanium into a planetary mixer, and stir for 1 hour at 40°C and vacuum -0.09MPa to obtain a dealcoholized silicone sealant.
[0072] Example 4
[0073] The preparation method of the low-humidity curing dealcoholized silicone sealant of this embodiment comprises the following steps:
[0074] S1: 100 parts of α,ω-dihydroxy polydimethylsiloxane with a viscosity of 50000 mPa·s, 9 parts of dimethyl silicone oil with a viscosity of 500 mPa·s, and 140 parts of 100 nanometer activated calcium carbonate were added to a planetary machine, mixed for 2 hours at 120°C and vacuum -0.095 MPa, and then cooled to 30°C to obtain a base material;
[0075] S2: 4 parts of methyltrimethoxysilane, 2 parts of propyl orthosilicate, and 1.1 parts of γ-aminopropylmethyldiethoxysilane were stirred and refluxed at 120° C. for 48 hours, and then cooled to 30° C. in a sealed container to obtain a mixed treated product;
[0076] S3: Add the above base material, 3 parts of modified silicone oil with a viscosity of 600mPa·s (structure as shown in Formula IV), the mixed treated material, 1.2 parts of hexapolyglycidyl ether oxypropyl methoxy silane (structure as shown in Formula I), and 4 parts of diisopropoxybis(ethoxyacetoacetyl)titanium into a planetary mixer, and stir for 1 hour at 40°C and vacuum -0.09MPa to obtain a dealcoholized silicone sealant.
[0077] Example 5
[0078] The preparation method of the low-humidity curing dealcoholized silicone sealant of this embodiment comprises the following steps:
[0079] S1: Completely the same as Example 1.
[0080] S2: 3 parts of methyltrimethoxysilane, 3 parts of polymethyltriethoxysilane and 1.2 parts of γ-glycidyloxypropyltrimethoxysilane were stirred and refluxed at 120° C. for 48 hours, and then the temperature was lowered to 30° C. in a sealed container to obtain a mixed treated product.
[0081] S3: Add the above base material, 2 parts of modified silicone oil with a viscosity of 500mPa·s (structure as Formula IV), the mixed treated product, 0.8 parts of hydroxy-terminated hexapolyaminoethyliminopropylmethylsilane (structure as Formula III), and 4 parts of diisopropoxybis(ethoxyacetoacetyl)titanium into a planetary machine, and stir at 40°C and vacuum -0.09MPa for 1h to obtain a dealcoholized silicone sealant.
[0082] Example 6
[0083] The preparation method of the low-humidity curing dealcoholized silicone sealant of this embodiment comprises the following steps:
[0084] S1: Completely the same as Example 1.
[0085] S2: 3 parts of methyltrimethoxysilane, 3 parts of polymethyltriethoxysilane and 0.8 parts of γ-glycidyloxypropyltrimethoxysilane were stirred and refluxed at 120° C. for 48 hours, and then the temperature was lowered to 30° C. in a sealed container to obtain a mixed treated product.
[0086] S3: Add the above base material, 2 parts of modified silicone oil with a viscosity of 500mPa·s (structure as Formula IV), the mixed treated product, 1.2 parts of hydroxy-terminated hexapolyaminoethyliminopropylmethylsilane (structure as Formula III), and 4 parts of diisopropoxybis(ethoxyacetoacetyl)titanium into a planetary machine, and stir at 40°C and vacuum -0.09MPa for 1h to obtain a dealcoholized silicone sealant.
[0087] Example 7
[0088] The preparation method of the low-humidity curing dealcoholization type silicone sealant of this embodiment comprises the following steps:
[0089] S1: Take 100 parts of α,ω-dihydroxypolydimethylsiloxane with a viscosity of 50000mPa·s, 6 parts of dimethyl silicone oil with a viscosity of 300mPa·s, and 120 parts of 100 nanometer activated calcium carbonate and add them into a planetary machine. Mix them for 2 hours at 120°C and vacuum -0.095MPa, and then cool them to 30°C to obtain a base material.
[0090] S2: 3 parts of methyltrimethoxysilane, 3 parts of polymethyltriethoxysilane and 1 part of γ-glycidyloxypropyltrimethoxysilane were stirred and refluxed at 120° C. for 48 hours, and then the temperature was lowered to 30° C. in a sealed container to obtain a mixed treated product.
[0091] S3: Add the above-mentioned base material, 1 part of modified silicone oil with a viscosity of 500mPa·s (structure as shown in Formula IV), the mixed treated material, 1 part of hydroxy-terminated hexapolyaminoethyliminopropylmethylsilane (structure as shown in Formula III), and 4 parts of diisopropoxybis(ethoxyacetoacetyl)titanium into a planetary mill, and stir at 40°C and vacuum -0.09MPa for 1h to obtain a dealcoholized silicone sealant.
[0092] Example 8
[0093] The preparation method of the low-humidity curing dealcoholization type silicone sealant of this embodiment comprises the following steps:
[0094] S1: Take 100 parts of α,ω-dihydroxypolydimethylsiloxane with a viscosity of 50000mPa·s, 4 parts of dimethyl silicone oil with a viscosity of 300mPa·s, and 120 parts of 100 nanometer activated calcium carbonate and add them into a planetary machine. Mix them for 2 hours at 120°C and vacuum -0.095MPa, and then cool them to 30°C to obtain a base material.
[0095] S2: 3 parts of methyltrimethoxysilane, 3 parts of polymethyltriethoxysilane and 1 part of γ-glycidyloxypropyltrimethoxysilane were stirred and refluxed at 120° C. for 48 hours, and then the temperature was lowered to 30° C. in a sealed container to obtain a mixed treated product.
[0096] S3: Add the above base material, 3 parts of modified silicone oil with a viscosity of 500mPa·s (structure as Formula IV), the mixed treated product, 1 part of hydroxy-terminated hexapolyaminoethyliminopropylmethylsilane (structure as Formula III), and 4 parts of diisopropoxybis(ethoxyacetoacetyl)titanium into a planetary machine, and stir at 40°C and vacuum -0.09MPa for 1h to obtain a dealcoholized silicone sealant.
[0097] Comparative Example 1
[0098] The preparation method of the low-humidity curing dealcoholized silicone sealant of this comparative example comprises the following steps:
[0099] S1: Completely the same as Example 1;
[0100] S2: Completely the same as Example 1;
[0101] S3; add the above base material, mixed treated material, 1 part of hydroxy-terminated hexaaminoethyliminopropylmethoxysilane, and 4 parts of diisopropoxybis(ethoxyacetoacetyl)titanium into a planetary mill, stir for 1 hour at 40°C and vacuum -0.09MPa to obtain a dealcoholized silicone sealant.
[0102] Comparative Example 2
[0103] The preparation method of the low-humidity curing dealcoholized silicone sealant of this comparative example comprises the following steps:
[0104] S1: Completely the same as Example 1;
[0105] S2: 3 parts of methyltrimethoxysilane, 3 parts of polymethyltriethoxysilane, and 2 parts of γ-glycidyloxypropyltrimethoxysilane were stirred and refluxed at 120° C. for 48 hours, and then cooled to 30° C. in a sealed container to obtain a mixed treated product;
[0106] S3: Add the above base material, 2 parts of modified silicone oil with a viscosity of 500 mPa·s, the mixed treated product, and 4 parts of diisopropoxydi(ethoxyacetoacetyl)titanium into a planetary mixer, and stir for 1 hour at 40° C. and vacuum -0.09 MPa to obtain a dealcoholized silicone sealant.
[0107] Comparative Example 3
[0108] The preparation method of the low-humidity curing dealcoholized silicone sealant of this comparative example comprises the following steps:
[0109] S1: Completely the same as Example 1;
[0110] S2; 3 parts of methyltrimethoxysilane, 3 parts of polymethyltriethoxysilane, and 2 parts of γ-glycidyloxypropyltrimethoxysilane were stirred and refluxed at 120°C for 48h, and the temperature was lowered to 30°C in a sealed container to obtain a mixed treated product;
[0111] S3: Add the above base material, the mixed treated product and 4 parts of diisopropoxybis(ethoxyacetoacetyl)titanium into a planetary mixer, stir for 1 hour at 40° C. and vacuum -0.09 MPa to obtain a dealcoholized silicone sealant.
[0112] Comparative Example 4
[0113] The preparation method of the low-humidity curing dealcoholized silicone sealant of this comparative example comprises the following steps:
[0114] S1: Completely the same as Example 1.
[0115] S2: Completely the same as Example 1.
[0116] S3: Add the above base material, 2 parts of modified silicone oil (structure as Formula IV) with a viscosity of 500mPa·s, the mixed treated material, 1 part of bis-[3-(triethoxysilyl)-propyl]-amine, and 4 parts of diisopropoxybis(ethoxyacetoacetyl)titanium into a planetary mixer, and stir for 1 hour at 40°C and vacuum -0.09MPa to obtain a dealcoholized silicone sealant.
[0117] Cure depth: Under low temperature and low humidity conditions (15°C, 15% RH), the test is carried out according to Method 2: Wedge groove method specified in GB / T 32369-2015 to obtain the cure depth. Tensile bond strength: The test piece is tested using a universal tensile testing machine. The prepared test piece is cured for 7 days under low temperature and low humidity conditions (15°C, 15% RH). The tensile adhesion test is carried out in accordance with GB / T13477.8-2017, and the average tensile strength is recorded and reported. The test results are shown in Table 1
[0118] Table 1 Performance test of silicone sealants prepared in various embodiments and comparative examples
[0119]
[0120]
[0121] *CF stands for cohesive failure, AF stands for adhesive failure
[0122] As can be seen from Table 1, Examples 1 to 8 use modified silicone oil and a crosslinking agent and coupling agent system of a specific process, and have a large curing depth, high initial strength, fast initial bonding speed, and good adhesion in a low-humidity environment. Comparative Example 1 does not use modified silicone oil, and the sealant has poor hygroscopicity, low crosslinking curing degree, small curing depth, and low initial strength. Comparative Example 2 does not use a coupling agent with a high concentration of functional groups, and its initial adhesion is poor, and the tensile bonding strength decreases. Comparative Example 3 uses neither modified silicone oil nor a coupling agent with a high concentration of functional groups. Its curing depth is small, the initial adhesion is poor, and the initial strength decreases significantly. Comparative Example 4 uses a silane monomer coupling agent with a high concentration of functional groups. Its hydrolysis coupling process consumes a lot of water and is slow, the initial adhesion is poor, and the tensile bonding strength decreases. It is fully explained that the present invention adopts hygroscopic modified silicone oil and a cross-linking agent coupling agent system of a specific process, and the obtained dealcoholized silicone sealant has a faster cross-linking curing speed, a faster initial bonding speed and a higher initial bonding strength in a low-humidity environment, which can meet the requirements of winter construction.
[0123] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A low-humidity curing dealcoholization type silicone sealant, characterized in that: The composition includes the following components in parts by weight: 100 parts of α,ω-dihydroxy polydimethylsiloxane, 70-140 parts of nano calcium carbonate, 3-10 parts of dimethyl silicone oil, 1-4 parts of modified silicone oil, 3-10 parts of composite cross-linking agent, 0.5-2 parts of coupling agent A, 0.5-1.5 parts of coupling agent B, 2-6 parts of titanate catalyst; Wherein, the coupling agent A is one or a mixture of γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane, γ-aminopropyltrimethoxysilane, and γ-aminopropylmethyldiethoxysilane; The coupling agent B is one or a mixture of epoxy silane oligomer and amino silane oligomer, and the structure of the coupling agent B is shown in the following formulas Ⅰ, Ⅱ, and Ⅲ, wherein n=0-4 in formula Ⅰ; n=0-4 in formula Ⅱ; and n=4-6 in formula Ⅲ; The mass ratio of the coupling agent A to the coupling agent B is 0.9-1.3:
1.
2. The low-humidity curing dealcoholization type silicone sealant according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 100 parts of α,ω-dihydroxy polydimethylsiloxane, 120-140 parts of nano calcium carbonate, 4-6 parts of dimethyl silicone oil, 1-2 parts of modified silicone oil, 5-7 parts of composite cross-linking agent, 0.8-1.5 parts of coupling agent A, 0.8-1.2 parts of coupling agent B and 3-5 parts of titanate catalyst.
3. The low-humidity curing dealcoholization type silicone sealant according to claim 2, characterized in that: The invention comprises the following components in parts by weight: 100 parts of α, ω-dihydroxy polydimethylsiloxane, 120 parts of nano calcium carbonate, 5 parts of dimethyl silicone oil, 2 parts of modified silicone oil, 6 parts of composite cross-linking agent, 0.8 parts of coupling agent A, 1.2 parts of coupling agent B and 4 parts of titanate catalyst.
4. The low-humidity curing dealcoholization type silicone sealant according to claim 1, characterized in that: The structure of the modified silicone oil is as shown in Formula IV:
5. The low-humidity curing dealcoholization type silicone sealant according to claim 4, characterized in that: The mass ratio of the dimethyl silicone oil to the modified silicone oil is 2.5 to 4:
1.
6. The low-humidity curing dealcoholization type silicone sealant according to claim 1, characterized in that: The viscosity of the α,ω-dihydroxy polydimethylsiloxane is 20000-80000 mPa·s; The particle size of the nano calcium carbonate is 50-200 nm.
7. The low-humidity curing dealcoholization type silicone sealant according to claim 1, characterized in that: The viscosity of the dimethyl silicone oil is 300-500 mPa·s; The modified silicone oil is polyethylene glycol modified hydroxy silicone oil with a viscosity of 300 to 800 mPa·s.
8. The low-humidity curing dealcoholization type silicone sealant according to claim 1, characterized in that: The titanate catalyst is one or a mixture of diisopropoxydi(ethoxyacetoacetyl)titanium, di-n-butoxydi(ethoxyacetoacetyl)titanium and tetraisopropionate titanate; The crosslinking agent is at least two of ethyl orthosilicate, propyl orthosilicate, polyethyl silicate, methyltrimethoxysilane, methyltriethoxysilane, and polymethyltriethoxysilane oligomer.
9. A method for preparing a low-humidity curing dealcoholization type silicone sealant as claimed in any one of claims 1 to 8, characterized in that: The steps include: S1: mixing α,ω-dihydroxy polydimethylsiloxane, dimethyl silicone oil and nano calcium carbonate to obtain a base material; S2: mixing the composite cross-linking agent and the coupling agent A to obtain a mixed treated product; S3: mixing the base material, modified silicone oil, the mixed treated product, coupling agent B, and titanate catalyst to obtain a low-humidity curing dealcoholization type silicone sealant.
10. The method for preparing the low-humidity curing dealcoholization type silicone sealant according to claim 9, characterized in that: Step S1 specifically includes the following steps: adding the α,ω-dihydroxy polydimethylsiloxane, the dimethyl silicone oil, and the nano calcium carbonate into a kneader at a temperature of 100° C. to 150° C. and a vacuum degree of -0.09 to -0.1 MPa, dehydrating and blending for 2 to 3 hours to obtain a base material, and cooling for standby use; Step S2 specifically includes the following steps: stirring and refluxing the composite cross-linking agent and the coupling agent A at 100° C. to 120° C. for 12 to 48 hours, and then cooling to 30° C. to 40° C. to obtain a mixed treated product; Step S3 specifically includes the following steps: at 10 to 30° C., adding the above-mentioned base material, the modified silicone oil, the mixed treated product, the coupling agent B, and the titanate catalyst into a planetary machine and stirring, stirring for 1 to 3 hours at a temperature of 30° C. to 50° C. and a vacuum degree of -0.09 to -0.1 MPa to obtain the low-humidity curing dealcoholization type silicone sealant.
Citation Information
Patent Citations
Dealcoholized silicone sealant and preparation method thereof
CN117447506A
Dealcoholized silicone sealant and preparation method thereof
CN112708393A
Dealcoholized silicone sealant as well as preparation method and application thereof
CN114032062A
Storage-stable single-component dealcoholized organosilicon sealant composition and preparation method thereof
CN117186832A
Rapid deep-curing weather-resistant organic silicon sealant and preparation method thereof
CN117467402A